Roots of Stylosanthes hamata create macropores in the compact layer of a sandy soil - Lesturgez, G.; Possl, R.; Hartmaan, C.; Bourdon, Emmanuel; Noble, A.D.; Ratana-Anupap, S. (2004)
The paper presents results of a field experiment designed to investigate the potential use of forage legume Stylosanthes hamata (stylo) to ameliorate the structure of a compact layer in sandy soils of Northeast Thailand. Sandy and acidic soils that are common to Northeast Thailand have restricted agronomic potential due to inherent chemical and physical properties. A compact layer at 20-40 cm reduces root elongation for most crops, thereby restricting the quantity of nutrients and water available for the plant growth. Deep ploughing and subsoiling are costly and have not been shown to be effective in overcoming compaction since these soils are unstable and collapse after the first heavy rainfall event. A three-year study was conducted in order to evaluate the effect of continuous stylo on the porosity of the compact layer and its influence on root elongation and yield of a subsequent maize crop. Continuous stylo was grown for two years in experimental plots and compared to a currently used stylo-maize rotation. Root distribution and macropore density were measured under the two cropping systems. After 24 months of continuous stylo, roots were able to penetrate the compact layer, resulting in a significant improvement in the macroporosity of this layer. The subsequent maize crop developed a deeper andmore extensive root system using macropores created after 24 months of continuous stylo when compared to the stylo-maize rotation treatment. This study demonstrates the potential role of Stylosanthes hamata in structural amelioration of sandy compact layers.